Female Genital Schistosomiasis and HIV: Research Urgently Needed to Improve Understanding of the Health Impacts of This Important Coinfection. (15th April 2019) - O'Brien, Daniel P.; Ford, Nathan; Djirmay, Amadou G.; Calmy, Alexandra; Vitoria, Marco; Jensen, Tomas O.; Christinet, Vanessa
Abstract : Abstract: Evidence suggests that there are important interactions between HIV and female genital schistosomiasis (FGS) that may have significant effects on individual and population health. However, the exact way they interact and the health impacts of the interactions are not well understood. In this article, we discuss what is known about the interactions between FGS and HIV, and the potential impact of the interactions. This includes the likelihood that FGS is an important health problem for HIV-positive women in Schistosoma -endemic areas potentially associated with an increased risk of mortality, cancer, and infertility. In addition, it may be significantly impacting the HIV epidemic in sub-Saharan Africa by making young women more susceptible to HIV. We call for immediate action and argue that research is urgently required to address these knowledge gaps and propose a research agenda to achieve this.